Potential and Superior Commodities of Peat Hydrology Area (PHA) of Ogan Komering Ilir Regency South Sumatra (Case Study : PHA Saleh River – Sugihan River) - Hamidah Hamidah; Marsi Marsi; M Umar Harun (Program Pascasarjana Universitas Sriwijaya, 2020)
Non-timber forest products (NTFPs) are a great potential in the forest, one of which is in the Saleh-Sugihan River Peat Hydrology Area (PHA). More optimal utilization of NTFPs is obtained with more diverse types of NTFPs, so it is important to know the diversity and potential of commodities in peatland areas for further development based on NTFPs. The research had been conducted from May to July 2018 in the PHA area of the Saleh-Sugihan Rivers, choosing Pangkalan Lampam District, Ogan Komering Ilir Regency, South Sumatra. Research sites include the villages of Air Rumbai, Deling, Lirik, Pangkalan Lampam, Rambai and Sukaraja. The research method is used by sampling, observation and interview methods. Determination of selected commodities uses analysis of Non-Timber Forest Products / NTFPs (Regulation of the Minister of Forestry of the Republic of Indonesia, 2009). Based on the results of the research that has been carried out, it is concluded that the leading commodity from the Peat Hydrology Area is swallow, paddy and fish, while the main commodity in Pangkalan Lampam sub-district is buffalo and purun. Leading commodity types of swallow, paddy, fish become NTFPs which are prioritized to be developed at the PHA River Saleh-Sugihan location, so that their development will be more focused and directed, in order to improve the regional economy.